Preparation and Characterization of Polypropylene-Natural Rubber/Clay Nanocomposites - Goh, Wei Chee (2007)
In this study, octadecylamine (ODA-MMT) and dodecylamine (DDA-MMT) modified natrium-montmorillonites (Na-MMTs) were used to prepare polypropylene-natural rubber /clay nanocomposites. The products were characterized using Fourier Transform Infrared (FTIR) spectroscopy, X-ray diffraction (XRD), Energy Filtering Transmission Electron Microscopy (EFTEM), Thermogravimetric Analyser (TGA) and tensile measurement. To prepare the nanocomposites, the ODA-MMT and DDA-MMT were blend with polypropylene and natural rubber in the ratio of 70: 30, by using an internal mixer. The study of blending speed, temperature and period shows that under the following blending conditions: 80 r.p.m. of rotor speed, temperature of 180oC and 6 minutes of blending period, the hybrid produced with maximum tensile strength and elongation at break was obtained. The optimum clay content to give maximum tensile strength is 1 php. In order to improve the mechanical properties of the blend, different amount of N, N’-m- phenylenedimaleimide (HVA-2) was blended with PPNR and their properties were also studied by tensile measurement, TGA and dynamic mechanical analysis (DMA). One php of HVA-2 was taken as the optimum concentration to be incorporated in PPNR because it gave the highest tensile improvement. The tensile properties and thermal degradation behaviour of PPNR/clay crosslinked with HVA-2 were then compared with the properties of PPNR/clay which consists of maleic anhydride grafted polypropylene (MAgPP) as a compatibilizer. HVA-2 crosslinked PPNR/clay shows higher tensile strength and elongation at break improvement compared to that of the MAgPP compatibilized PPNR/clay. However, the TGA thermograms of these two systems are very similar. The PPNR/HVA-2/clay nanocomposites were further modified by changing their clay contents. XRD and TEM analyses show that octadecylamine modified montmorillonite (ODA-MMT) and dodecylamine modified montmorillonite (DDA-MMT) produce a mixture of intercalation and flocculation, and of intercalation and exfoliation in the hybrids, respectively. By incorporating 1 and 2 php of ODAMMT into the HVA-2 crosslinked PPNR, the tensile strength of the hybrid increases about 10%. One php of DDAMMT clay loaded in the blend causes 7% of increment in tensile strength. The thermal degradation of both organoclay loaded blends is almost the same as the sample with the low clay content. Increase the modified clay content to 5 php improves the degradation temperature of 20oC.